Mutasi Sekda Jepara ke Diskarpus dalam Perspektif Permenpan RB No. 15 Tahun 2019 - Albab, Ulul; Febritah Zalfaa Nabilah; Muhammad Rifki Ferdinan; Dwi Wirayudha; Rania Nurhalisa (Taruna Law: Journal of Law and Syariah, 2025)
This study examines the administrative legal implications of the transfer of the High Leadership Position (JPT) from Regional Secretary (Sekda) of Jepara to Head of the Archives and Library Office (Diskarpus), focusing on potential violations of meritocracy, legality, and transparency principles in civil servant management. The research aims to assess the compliance of the transfer process with the provisions of Ministry of Administrative and Bureaucratic Reform Regulation No. 15 of 2019 on Open and Competitive Filling of JPT, and to evaluate its impact on the integrity of local government governance. The study employs a normative juridical approach with an analysis of relevant legislation and a case study of the Sekda Jepara transfer. Findings reveal that the transfer was conducted without an open selection process, lacked recommendation from the Civil Service Commission (KASN), and disregarded the evaluation of qualifications and competencies as mandated by the merit system. These findings indicate violations of the principles of good governance, particularly legality, due diligence, and protection of civil servants’ rights, potentially leading to maladministration and reduced public accountability. Therefore, this study recommends strengthening external oversight by KASN, enhancing regulatory understanding among personnel authorities, and comprehensive reform of transfer governance to ensure legality, transparency, and accountability.